Antagonistic Activities of Epiphytic Bacteria on Black Pod Disease of Cocoa - Mohd Jaaffar, Ahmad Kamil (2004)
A study was conducted to determine the antagonistic activity of epiphytic bacteria isolated from cocoa pod surface on Phytophthora palmivora (Butler) Butler, the causal agent of black pod disease of cocoa. Out of 233 isolates of epiphytic bacteria obtained from non symptomatic and diseased cocoa pods, only were found to have antagonistic activities against the fungal pathogen when screened by the dual-culture method. Three isolates, (LKM/B/1, LKM/B/35, LKM/B/76c) were identified as Pseudomonas putida Biotype A, 2 isolates (LKM/B/5 and LKM/B/62b) were identified as Pseudomonas aeruginosa and one isolate each was identified as Pseudomonas spinosa (LKM/B/2), Burkholderia glidioli (LKM/B/4) and Burkholderia sp (LKM/B/6). Identification of the epiphytic bacteria was done using the BIOLOG® Identification System. Percentage inhibition of the radial growth (PIRG) of P. palmivora by the epiphytic bacteria ranged from 66.0% to 82.1%. All isolates of epiphytic bacteria showed optimum antagonistic activities at 300 C. pH has no influence on the antagonistic activities of the epiphytic bacteria. Detached pod studies showed that pods treated with the epiphytic bacteria retarded the growth of black pod lesion up to 12 days after inoculation. Isolate Burkholderia glidioli (LKM/B/4), Pseudomonas aeruginosa (LKM/B/5) and Pseudomonas putida Biotype A (LKM/B/76c) produced volatile substances that affect the growth of P. palmivora, while isolates LKM/B/1 and LKM/B/35 of Pseudomonas putida Biotype A and isolate LKM/B62b of Pseudomonas aeruginosa did not show the production of volatile substances. Isolate LKM/B/76c also produced diffusible metabolites that could significantly inhibit the growth of P. palmivora compared to other epiphytic bacteria especially isolate LKM/B/35 which showed good antagonistic through dual culture method. Microscopic observations of P. palmivora at the periphery of the inhibition zone indicated that all isolates of epiphytic bacteria inhibited P. palmivora by the process of cell wall degradation and growth retardation.